IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 1 BANGIL: IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 1 BANGIL - Rokim, Rokim; Zakariyah; Waslah; Moh.Kholik (Universitas Islam Lamongan, 2024)
The purpose of this study was to determine how to implement the Independent Curriculum in Islamic Religious Education and Character Education subjects at SMA Negeri 1 Bangil, starting from how to implement the Independent Curriculum which consists of teacher preparation, implementation methods and assessment methods, then problems that occur and efforts made by educators in implementing the Independent Curriculum in Islamic Religious Education and Character Education subjects. We already know that the Independent Curriculum is a new curriculum with a foundation as a refinement of the 2013 Curriculum, but in implementing this Independent Curriculum, it is necessary for teachers to apply it first before teaching it to students. So that it can build quality student character both in academics and in other fields. This study uses a descriptive qualitative approach by taking SMA Negeri 1 Bangil as the object. Data collection techniques are carried out through observation, interviews and documentation. Respondents in this study were the principal, curriculum vice principal, Islamic Religious Education and Character Education teachers for class X and students who understand this research. The results of this study indicate that the implementation of Islamic Religious Education and Character Education learning consists of 3 activities, the first is an introductory activity, then the core activity and is closed with a closing activity, plus the P5 project. Then there are problems that occur in the implementation of Islamic Religious Education and Character Education learning, namely educators do not participate in training, differentiated learning is not optimal and mindset. So that the efforts made to overcome these problems are by participating in internal/external workshops, increasing creativity as a teacher and sharing with fellow educators or people who know more (often ask questions)